Development and application of NMR spectroscopy in G-quadruplexes : structure, dynamics and formation in biofilm - Winnerdy, Fernaldo Richtia (Nanyang Technological University, 2019)
G-quadruplex is a secondary non-canonical structure of nucleic acid which gained popularity due to increasing evidence of its biological functions, potential therapeutic prospects and nanotechnology applications. Encouraged for a better comprehension of G-quadruplex as an alternative DNA structures, we address multiple angles of G-quadruplex properties including its dynamics, ligand binding kinetics, numerous novel topologies and potential role in biofilm networking. This research was accomplished through a combination of biophysical techniques, primarily Nuclear Magnetic Resonance (NMR) spectroscopy.